The clinical differences between traumatic and NOS chronic subdural hematoma - Yang, Yongxiang; Zhu, Xiansong; Yang, Tao; Fan, Kexia; Cheng, Jingmin; Ma, Yuan (Frontiers in Neurology, 2024)
Abstract Objective Chronic subdural hematoma (CSDH) is a common neurologic disorder with increasing incidence, which can be preceded by head trauma or occur in the absence of trauma. In order to deeply understand the clinical characteristics of this disease, we conducted this retrospective study to explore the clinical differences between traumatic and not otherwise specified (NOS) CSDH. Methods According to the inclusion and exclusion criteria, 168 traumatic CSDH patients and 133 NOS CSDH patients were recruited from January 2015 to October 2023 in our cohort. The collected data and compared parameters including baseline clinical features and radiological outcomes of hematoma within 24h of hospital admission, as well as the treatment method and clinical outcome of traumatic and NOS CSDH patients. Results Compared to NOS CSDH patients, the average age was younger, epilepsy was more frequent, asymptomatic cases were more common, and the taking of anticoagulants and antiplatelet drugs were rarer in traumatic CSDH patients (all P＜0.05). However, no differences were found in the radiological presentations of hematoma at admission, the treatment methods and clinical outcomes of traumatic and NOS CSDH patients (all P＞0.05). Conclusion Traumatic CSDH patients were more likely to be asymptomatic or have seizures, while NOS CSDH were more common in elder people and in individuals with the history of taking anticoagulants and antiplatelet drugs. The treatment methods and clinical outcomes were similar in traumatic and NOS CSDH patients.